2015
DOI: 10.1016/j.jviromet.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the swab sampling method to recover viruses from fomites

Abstract: The monitoring of virus contamination on fomites, especially at hospitals has been used for a more effective evaluation of the microbiological quality of surfaces. Swab sampling is the method used currently, although the use of an internal control process (ICP) has not yet been assessed. The aim of this study is to determine the recovery rate of murine norovirus 1 (MNV-1) and bacteriophage PP7 on different surfaces in order to assess their potential use as an ICP. For this purpose both viruses were spiked expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The authors found recoveries for both hNoV and rotavirus to be higher from FCS than food surfaces at both inoculum concentrations (Scherer et al, 2009). Additionally, Ganime et al, (2015) evaluated the recovery rates of MNV-1 and bacteriophage PP7 from porous formic, non-porous formic, and rubberized surfaces using a rayon swab with culture media with recovery efficiencies ranging from 0.6 to 11.5% (PP7) and 12.2-77.0% (MNV-1). While these two studies evaluate how one particular swab performs, other studies expand their evaluations to provide a better comparison of different swabs and tools and their recovery of particular enteric viruses.…”
Section: Swabbingmentioning
confidence: 99%
“…The authors found recoveries for both hNoV and rotavirus to be higher from FCS than food surfaces at both inoculum concentrations (Scherer et al, 2009). Additionally, Ganime et al, (2015) evaluated the recovery rates of MNV-1 and bacteriophage PP7 from porous formic, non-porous formic, and rubberized surfaces using a rayon swab with culture media with recovery efficiencies ranging from 0.6 to 11.5% (PP7) and 12.2-77.0% (MNV-1). While these two studies evaluate how one particular swab performs, other studies expand their evaluations to provide a better comparison of different swabs and tools and their recovery of particular enteric viruses.…”
Section: Swabbingmentioning
confidence: 99%
“…Herzog et al (2012) demonstrated that the SRE of bacteriophage P22 applied to a number of different fomites under a variety of conditions was most influenced by sampling time, fomite surface area, wetting agent use, and relative humidity [135]. Ganime et al (2015) evaluated swab sampling as a method to recover murine norovirus 1 (MNV-1) and bacteriophage PP7 from porous, non-porous, and rubberized fomite surfaces, finding a highly variable recovery efficiency ranging from < 1 to 77% [136]. Weir et al (2016) demonstrated the impact that variability in fomite recovery from surfaces using different sampling methods can have on QMRA model results [21•].…”
Section: Improving Model Inputsmentioning
confidence: 99%
“…Knowledge of the role of personnel in the indirect transmission of viruses may be of importance for understanding the dynamics of viral infections. For example, monitoring surfaces has been shown to be essential to understand the dissemination of viruses in hospitals or day-care centers, and it has helped to establish preventive measures [ 20 , 21 ]. In order to determine the dynamics of virus survival and transmission via contaminated PPE and the attendant health risks, levels of viral contamination on PPE need to be quantified [ 13 ].…”
Section: Discussionmentioning
confidence: 99%